Carboxypeptidase A4 promotes cardiomyocyte hypertrophy through activating PI3K-AKT-mTOR signaling. Issue 5 (11th May 2020) - Gao, Weinian; Guo, Na; Zhao, Shuguang; Chen, Ziying; Zhang, Wenli; Yan, Fang; Liao, Hongjuan; Chi, Kui
Abstract: Carboxypeptidase A4 (CPA4) is a member of the metallocarboxypeptidase family. Current studies have identified the roles of CPA4 in cancer biology and insulin sensitivity. However, the roles of CPA4 in other diseases are not known. In the present study, we investigated the roles of CPA4 in cardiac hypertrophy. The expression of CPA4 was significantly increased in the hypertrophic heart tissues of human patients and isoproterenol (ISO)-induced hypertrophic heart tissues of mice. We next knocked down Cpa4 with shRNA or overexpressed Cpa4 using adenovirus in neonatal rat cardiomyocytes and induced cardiomyocyte hypertrophy with ISO. We observed that Cpa4 overexpression promoted whereas Cpa4 knockdown reduced ISO-induced growth of cardiomyocyte size and overexpression of hypertrophy marker genes, such as myosin heavy chain β ( β-Mhc ), atrial natriuretic peptide ( Anp ), and brain natriuretic peptide ( Bnp ). Our further mechanism study revealed that the mammalian target of rapamycin (mTOR) signaling was activated by Cpa4 in cardiomyocytes, which depended on the phosphoinositide 3-kinase (PI3K)-AKT signaling. Besides, we showed that the PI3K-AKT-mTOR signaling was critically involved in the roles of Cpa4 during cardiomyocyte hypertrophy. Collectively, these results demonstrated that CPA4 is a regulator of cardiac hypertrophy by activating the PI3K-AKT-mTOR signaling, and CPA4 may serve as a promising target for the treatment of hypertrophic cardiac diseases.